2019
DOI: 10.3390/molecules24193517
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Antioxidant, Anti-Aging and Organ Protective Effects of Sulfated Polysaccharides from Flammulina velutipes

Abstract: As an irreversible and complex degenerative physiological process, the treatment for aging seems strategically necessary, and polysaccharides play important roles against aging owing to their abundant bioactivities. In this paper, the antioxidant and anti-aging activities of Flammulina velutipes polysaccharides (FPS) and its sulfated FPS (SFPS) on d-galactose-induced aging mice were investigated. The in vitro antioxidant activities demonstrated that SFPS had strong reducing power and superior scavenging effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 55 publications
1
45
0
1
Order By: Relevance
“…Flammulina velutipes is one of the most popular edible mushrooms that contain triterpenes, polysaccharides, sterols and vitamins. F. velutipes polysaccharides have anti-inflammatory, antioxidant, anti-aging, immune modulatory, and intestinal flora activities (7)(8)(9)(10). Earlier experiments of our group found that F. velutipes polysaccharides were non-toxic and could promote intestinal motility and improve constipation in rats (11).…”
Section: Introductionmentioning
confidence: 94%
“…Flammulina velutipes is one of the most popular edible mushrooms that contain triterpenes, polysaccharides, sterols and vitamins. F. velutipes polysaccharides have anti-inflammatory, antioxidant, anti-aging, immune modulatory, and intestinal flora activities (7)(8)(9)(10). Earlier experiments of our group found that F. velutipes polysaccharides were non-toxic and could promote intestinal motility and improve constipation in rats (11).…”
Section: Introductionmentioning
confidence: 94%
“…The method of scavenging DPPH free radicals has been widely used to study the antioxidant capacity of a substance [ 33 ]. Figure 9 A shows that, regarding the DPPH scavenging ratio in the concentration range of 40 ug·mL −1 to 120 ug·mL −1 , the DPPH scavenging ratio was increased with the increasing concentration of EAS and ASTFs, and, when the concentration of EAS and ASTF was 200 ug·mL −1 , the scavenging ratio reached 88.91% and 90.56%.…”
Section: Resultsmentioning
confidence: 99%
“…The SOD is a naturally occurring superoxide free radical scavenger that converts harmful superoxide radicals into hydrogen peroxide [34]. A recent study conducted by Yuan and colleagues [35] on the anti-aging, antioxidant, and organ-protective potential of Flammulina velutipes polysaccharide correlated severe oxidative damage with the decrease in SOD, glutathione peroxidase, and other enzymes and increase in MDA levels. Further, the results of this work revealed that the treatment with sulfated polysaccharide significantly enhanced the antioxidant enzymes and reduced lipid peroxidation products.…”
Section: Discussionmentioning
confidence: 99%